YSZ-Based Oxygen Sensors and the Use of Nanomaterials: A Review from Classical Models to Current Trends. (19th October 2009) - López-Gándara, Carlos; Ramos, Francisco M.; Cirera, Albert
Abstract : This work reviews physicochemical models on the operation and the response of potentiometric oxygen gas sensors based on ion-conducting electrolytes. The aim for describing the electric response and some properties like response time, ionic conductivity, catalytic activity, or gas selectivity of these devices has led to the development of some models in the last decades. These models have provided information on relations between the response of the sensors, their design and fabrications process, and some morphological properties, like grain size of the electrolyte, diffusion on protective layers, or density of three-phase boundary points in the measuring electrodes. Current trends on improving catalysis, gas selectivity, and activation energy for ion conducting by using nanomaterials are described as well.